CDS : Community Design Solutions, 2015-2017 - (:unkn) unknown (My University, 2017)
Community Design Solutions (CDS) is a funded design center at the School of Architecture & Urban Planning, UW-Milwaukee that assists communities, agencies, civic groups, and campuses throughout Wisconsin. CDS provides preliminary design and planning services to underserved communities and agencies. Students from SARUP work with Director, Carolyn Esswein, clients and faculty to develop concepts that promote positive change, stimulate funding opportunities, and serve as a catalyst for continued investment. Represented projects 2015-2017